Autoimmune hepatitis and acquired partial lipodystrophy. Issue 2 (14th May 2021) - Bakewell, Christopher; Dayasiri, Kavinda; Brown, Rachel M; Rodrigues, Astor; Williams, Rachel; Anand, Geetha; Gupte, Girish L
Abstract : The lipodystrophies are an extremely rare group of metabolic conditions which are categorised based on their pathogenesis and phenotype. While primarily known for the striking loss of subcutaneous adipose tissue which they induce, they may also be associated with significant liver injury. In most cases, this results from the secondary deposition of lipid within hepatic parenchyma and is seen predominantly in generalised lipodystrophy. More rarely, patients may develop autoimmune hepatitis. We report a rare case of a 17-month-old boy who developed features of acquired partial lipodystrophy in association with anti-LKM1-positive autoimmune hepatitis following initial presentation with a Henoch-Schönlein purpura-like illness. We describe his challenging path to diagnosis and discuss his ongoing management in an effort to further our understanding of this rare but significant association. This report highlights the need for close clinical observation and a high index of suspicion for recognising early features of lipodystrophy.